Estrogen receptor modulators genistein, daidzein and ERB-041 inhibit cell migration, invasion, proliferation and sphere formation via modulation of FAK and PI3K/AKT signaling in ovarian cancer - Karen K. L. Chan; Michelle K. Y. Siu; Yu-xin Jiang; Jing-jing Wang; Thomas H. Y. Leung; Hextan Y. S. Ngan (Cancer Cell International, 2018)
Abstract Background Ovarian cancer is the most lethal gynaecological malignancy. Chemotherapy is the main stay of treatment for metastatic disease, with modest response rates but significant side effects. Therefore, there is a need for alternative therapies that can control the disease while offering good quality of life. Ovarian cancer cells express both estrogen receptor subtypes (ERα and ERβ). There is growing evidence that ERβ is anti-oncogenic. Genistein and daidzein are phytoestrogens found in soybeans and they display higher affinity to bind ERβ. ERB-041 is a potent selective ERβ agonist. In this study, we aimed to investigate the effects of genistein, daidzein and ERB-041 on ovarian cancer. Methods Ovarian cancer cell lines were treated with genistein, daidzein and ERB-041 in pharmacological doses. Cell migration, invasion, proliferation, cell cycle arrest, apoptosis and sphere formation were assessed by Transwell migration and invasion assays, XTT assay, focus formation, flow cytometry and sphere formation assay, respectively. Immunoblotting analysis was performed to determine the downstream signaling pathways. Results We found that genistein, daidzein and ERB-041 significantly inhibited ovarian cancer cell migration, invasion, proliferation, as well as induced cell cycle arrest and apoptosis. Significantly inhibitory effect on the size and number of sphere formed in genistein, daidzein and ERB-041 treated cells was also demonstrated. Moreover, genistein, daidzein and ERB-041 treatment reduced p-FAK, p-PI3K, p-AKT, p-GSK3β, p21 or cyclin D1 expression in ovarian cancer cells. Conclusion Genistein, daidzein and ERB-041 decreased ovarian cancer cell migration, invasion, proliferation and sphere formation, and induced cell cycle arrest and apoptosis with altered FAK and PI3K/AKT/GSK signaling and p21/cyclin D1 expression, suggesting their roles on ovarian cancer cell metastasis, tumorigenesis and stem-like properties and their potential as alternative therapies for ovarian cancer patients.